A Tear by Nicky Manuputty: a Review of Alto Saxophone Playing Techniques and the Meaning of the Work - Teddy Nicolas Silalahi; Junita Batubara (Universitas Negeri Medan, 2023)
A TEAR is a work of Nicky Manupputty who is a Saxophonist. The uniqueness of this song is that Nicky Manuputty uses a distinctive and different tounging. He has his own characteristics in playing saxophone in this work, namely tounging techniques resembling 'del-del' and resembling 'ta-ya' tounging. Therefore, the author is interested in researching the work A TEAR. The author found the technique of combining 'del-del' and 'ta-ya' tounging. The technique is the